A RULE-BASED MORPHOLOGICAL ENGINE FOR UZBEK LANGUAGE - Zulunov Ravshan,Ismailov Alisher Shakirovich (International Journal of Literature and Language Studies, 2026)
Current computational processing of Uzbek language is delayed by the limitations of